Kilka uwag o nowogródzko-czombrowskich kontaktach językowo-kulturowych utrwalonych w "Impresjach czombrowskich" Zofii Brzozowskiej i "Dziedziczkach Soplicowa" Joanny Puchalskiej = A few remarks on the Navahrudak-Czombrów linguistic-cultural relations preserved in "Impresje czombrowskie" by Zofia Brzozowska and "Dziedziczki Soplicowa" by Joanna Puchalska - Węgorowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is devoted to discussing issues related to the Grand Duchy of Lithuania and Polish Northeastern Borderlands - a border area whose multiethnicity, multiculturalism, multireligiousness and multilingualism have been preserved in separate accounts of two descendants of the Karpowicz clan who were the last owners of the Czombrow estate in the Navahrudak area, the literary equivalent of Mickiewicz`s Soplicowo.
Keywords: Wielkie Księstwo Litewskie; Kresy Północno-Wschodnie; pogranicze; kontakty językowo-kulturowe; wieloetniczność; wielokulturowość; wieloreligijność; wielojęzyczność; the Grand Duchy of Lithuania; Polish Northeastern Borderlands; border area; linguistic-cultural relations; multiethnicity; multiculturalism; multireligiousness; multilingualism